Cross-Industry Determinants of Capital Structure: Evidence from Malaysia Public-Listed Companies - Kok, Wai Cheng (2023)
The main objective of this thesis is to investigate the determinants of capital structure of the firms in the Malaysian capital market for seven sectors; this paper aims to study how capital structure differs across the industry in Malaysian public listed companies. New evidence from sector-specific panel models; and the conclusions in this study; firstly, the firms’ profitability is the most important determinant, followed by firm size and GDP, and the determinants of capital structure differ between industries, according to new sector-specific models. These findings add to the stylized facts of sectorspecific capital structure factors. Secondly, the paper investigates whether capital structure differs between large and small firms. Evidence from Malaysian Public Listed Companies; the study aimed to examine the capital structure and the leverage used in Malaysian public listed firms. This study examines firms' capital structure in the Malaysian stock market. Based on 265 non-financial firms from the seven sectors between 2010–2018, our sample firms are further divided into small and large firms. Our results show that, on average, small firms recorded more leverage than large firms, except for the plantation and property sectors. Second, the Fixed Effect Model with a robust standard error, Quantile regression, and system GMM model show that profitability and size are significant for large and small firms. Lastly, sector-specific models show that the most important determinants are profitability, followed by firm size and GDP growth. These new sector-specific models show that the determinants of capital structure differ across different industries. These findings contribute to the stylized facts of sector-specific determinants of capital structure concerning large and small firms. Thirdly, the paper studies the nexus between financial leverage and board independence of public-listed firms: is there any stylized fact? This study examines the relationship between financial leverage and board independence for firms listed in the Malaysian stock market. Based on a sample of 265 non-financial firms listed on Bursa Malaysia from 2014 to 2018. These results indicate the importance of independent directors for old, large, or low-profitability firms in reducing their financial leverage. These findings highlight the relevance of independent directors in decreasing financial leverage for old, large, or low-profit companies. These findings support the stylized facts of the link between financial leverage and board independence. This study makes several significant contributions to existing capital structure studies. This work contributed to the development of a model of determinants of the capital structure by combining factors relevant to the businesses, culture, shareholders, policymakers, and manager behavior. This research also offers insight into shareholder and managers' financing preferences with appropriate implementations for researchers, investors, financial providers, and policy makers. The research results will assist shareholders and managers in making optimal capital structure decisions, and policymakers will make effective financing policies.